ESTIMASI PENAWARAN BIAYA PENGEDOKAN KAPAL PADA GALANGAN XYZ MENGGUNAKAN METODE REGRESI LINIEAR - Achmad Yoansyah Syah; Ali Azhar (JURNAL JALASENA, 2022)
Shipbuilding company is a company engaged in the field of new ship construction services and ship repair, and has facilities for work on water. Before doing repairs. Factors that affect the general cost of docking ships are the main size of the ship and other data. As in the case study of the XYZ Shipyard, there is still a cancellation of the negotiation of general docking costs, due to the different calculation of docking costs. The purpose of this study was to determine the value of the public docking cost offer using the multiple linear regression method according to the main size of the ship (L, B, D) and the estimated duration of repair work and then an analysis of the effect of each variable used for the estimation of docking costs will be carried out. It is hoped that this research can be useful for shipyards and ship owners in estimating the optimal general cost of docking so that project cancellations do not occur and negotiations run smoothly.